Probability, Probability and Plausibility: Understanding Concepts in the Philosophy of Aristotle Farabi, Averroes and Avicenna - Nurfer Tercan; Gulzhikhan Nurysheva; Nurlan Baigabylov (Migration Letters, 2023)
The aim of this study, based on the concepts of Aristotle, Al Farabi, Ibn Sinai and Ibn Rushdi, is to target both the tradition of Islamic philosophy and the history of ideas about mathematics and metaphysics, with the insights of all three philosophers. However, logic is to contribute to these problems in the modern definition of logical problems and solutions within the framework of the Islamic philosophy. Significantly, the classical logic indicated that probability calculation existed, and mentioned the distinction between Aristotle and Avicenna in their approach to the concept of possibility. The purpose of this paper is to examine what terms and concepts these words are, and to frame for a more detailed review of the history of ideas, the causation of the phenomenon, and the context of the medieval era. Rather than considering a large part of the relationship between logic and metaphysics, one could argue that examining these concepts in an environment in which they are closely related would create a remarkable weight on one side. When exploring the metaphysical understanding of philosophers, these concepts were not presented in the study of logic, especially their definition and classification. The main purpose of this study is to point out that there is a possibility and probability in the part of the efforts of Islamic philosophers to understand metaphysical ideas and to demonstrate the meaning and use of this concept.